Groundwork for a New Kind of African Metaphysics: The Idea of Predeterministic Historicity, by Aribiah David Attoe - Agada, Ada (Phronimon, 2022)
Palgrave Macmillan, 2022, 117 + xxii ISBN: 978-3-030-91109-6